Case report: Intraosseous hibernoma (IOH) mimics osseous metastasis: another rare pitfall in FDG-PET-CT - Stolte, Sebastian J.; Geiger, Hanna; Forrer, Flavio; Rodriguez, Regulo; Müller, Joachim (Frontiers in Nuclear Medicine, 2023)
Intraosseous hibernoma (IOH) mimicking osseous metastasis is a rare and little-known pitfall in nuclear medicine and radiology. Referring to a clinical case we show imaging features in FDG-PET, CT as well as pathological characteristics and discuss MRI and differential diagnoses. A 73-year old woman was assigned for FDG-PET/CT examination after the incidental finding of a suspicious pulmonary nodule. FDG-PET/CT detected a small slightly FDG-avid pulmonary nodule suspect for malignancy and a small sligthly sclerotic lesion with mild FDG-uptake in the upper pubic bone. Histopathology revealed an intraosseous hibernoma, a rare benign soft tissue tumor arising from brown fat. In the few literature available intraosseous hibernomas may or may not be positive on bone scans. Like in our case most are slightly sclerotic on CT but also lytic lesions have been described. In MRI they are T1 hypointense to subcutaneous fat and hyperintense to skeletal muscle; they are usually T2 hyperintense and may show peripheral contrast enhancement. According to literature IOH are mostly incidental findings with solitary lesions in spine, pelvis, ribs or very rarely in extremities with low to moderately increased glucosemetabolism. IOH present as painless tumors in general; a few painful cases could be successfully treated with RFA or surgery. Differential diagnoses include metastases, lymphoma, fibrous dysplasia, non ossifying fibroma and more. Intraosseous hibernoma is a rare benign tumor which can mimic metastases in FDG-PET, CT, bone scan and MRI. IOH might be indistinguishable from metastases or malignant lesions which makes biopsy or follow-up mandatory in clinically relevant cases. Given the benign nature of IOH, radiofrequency ablation or surgery is only an option in symptomatic cases.